إزالة الرصاص والزنك من المياه الصناعية باستخدام زيوليت طبيعي /فليبسايت/ من جنوبي سوريا - هناء سلمان; هيثم شاهين; غياث شاهين; نسرين خلوف (Tishreen University, 2017)
أجريت هذه الدراسة لإزالة المعادن الثقيلة (Zn2+, Pb2+ ( في حالات السكون من المحاليل المائية الأحادية والمتعددة المكونات باستخدام الزيوليت الطبيعي السوري. بينت الدراسة أن هذه الإزالة لها طبيعة تبادل أيوني وتتألف من ثلاث مراحل هي: الامتزاز على سطح البلورات الميكروية، مرحلة التحول، الامتزاز المحدود داخل البلورات الميكروية. بينت الدراسة أن الزمن اللازم لحصول التوازن هو 6 ساعات، وأن الاختلاف البسيط بين سعات امتزاز الزيوليت بالنسبة للرصاص والزنك من المحاليل الأحادية والمتعددة المكونات يثبت وجود مراكز امتصاص فردية للزيوليت من أجل كل معدن. قيست سعة الامتصاص القصوى بالنسبة لـ pb2+ وهي 33.89 mg/g عند التركيز التوازني 261.07 mg/l ، وبالنسبة لـ Zn2+ كانت 29.18 mg/g عند 309.818 mg/l . تم استخدام نماذج خطوط تبادل امتزاز Langmuir وFreundlich لتقييم أداء امتزاز الزيوليت الطبيعي للرصاص والزنك. كانت هذه النماذج قادرة على تقديم ملاءمة جيدة مع البيانات التجريبية، مع معامل ارتباط R2 يتراوح بين 0.95-0.99، مع ملائمة أفضل لنموذج لانغموير. The study was carried out on the sorption of heavy metals (Pb+2, Zn+2) under static conditions from single- and multicomponent aqueous solutions by Syrian Zeolite mineral extracted from south Syria. The removal has an ion-exchange nature and consists of three stages: the adsorption on the surface of microcrystals, the inversion stage, and the moderate adsorption in the interior of the microcrystal, The study showed that equilibrium time is 6 hours, and The slight difference between adsorption capacity of the Zeolite toward lead, zinc from single- and multicomponent solutions may testify to individual sorption centers of the zeolite for each metal. The maximum sorption capacity toward pb2+ is determined as 33.89 mg/g at an equilibrium concentration of 261.07 mg/L and toward Zn+2 as 29.18 mg/g at 309.818 mg/L. Langmuir and Freundlich Adsorption Isotherms were used to evaluate natural zeolite adsorption performance for Lead, Zinc. These Isotherms were able to provide suitable fit with experimental data, the factor R2 ranged between 0.95 - 0.99, with better fit to Langmuir Isotherm.